Stem cell homing in periodontal tissue regeneration - Meng, Lingxi; Wei, Yige; Liang, Yaxian; Hu, Qin; Xie, Huixu (Frontiers in Bioengineering and Biotechnology, 2022)
The destruction of periodontal tissue is a crucial problem faced by oral diseases, such as periodontitis and tooth avulsion. However, regenerating periodontal tissue is a huge clinical challenge because of the structural complexity and the poor self-healing capability of periodontal tissue. Tissue engineering has led to advances in periodontal regeneration, however, the source of exogenous seed cells is still a major obstacle. With the improvement of in situ tissue engineering and the exploration of stem cell niches, the homing of endogenous stem cells may bring promising treatment strategies in the future. In recent years, the applications of endogenous cell homing have been widely reported in clinical tissue repair, periodontal regeneration, and cell therapy prospects. Stimulating strategies have also been widely studied, such as the combination of cytokines and chemokines, and the implantation of tissue-engineered scaffolds. In the future, more research needs to be done to improve the efficiency of endogenous cell homing and expand the range of clinical applications.